When the “Weaker Sex” became the “Beauty symbol” – The Feminine Beauty in the Romanian Interwar Press - Fănel Teodoraşcu (EIRP Proceedings, 2018)
Among the important changes brought about by the early years of the interwar period in the life of the woman was the fact that she, the woman, was no longer regarded as the “weak” half of man, as it had been before, but the “beautiful” half. Another feature of the interwar era is that beauty is no longer old. The desire of the interwar woman, regardless of her social status or her age, of being always beautiful was explained by the fact that a beautiful woman was easier to find a job or get into the business world. For some journalists, lipstick and last fashion clothes were specific to women of mild morals. Most of the texts used for this paper were published in the years between the two world wars.